Konsekuensi Yuridis Penerapan Yurisdiksi Mahkamah Pidana Internasional Terhadap Eksistensi Pengadilan Nasional dalam Mengadili Kejahatan Internasional - Ibnu Mardiyanto (Pusat Penelitian Badan Keahlian Setjen DPR RI, 2023)
The application of the jurisdiction of the International Criminal Court has consequences for the role of national courts in adjudicating international crimes. The International Criminal Court possesses the authority to prosecute specific offenses, including genocide, crimes against humanity, war crimes, and crimes of aggression. However, the establishment of the International Criminal Court does not absolve national courts of their obligation to investigate and prosecute the perpetrators of these crimes. This study examines the legal implications as consequences of the jurisdictional application of the International Criminal Court on the role of national courts in adjudicating international criminals. The research methodology employed in this study is normative research. This research’s findings demonstrate that the application of the International Criminal Court’s jurisdiction is of utmost importance in addressing impunity for international crimes and is a pertinent global concern. The International Criminal Court functions as a supplementary body and only intervenes when national courts are unable to carry out their duties effectively. The legal ramifications of exercising the jurisdiction of the International Criminal Court alongside national courts necessitate collaboration and coordination between the two entities to ensure a fair and effective outcome for both the accused and the victims. Therefore, it is imperative to promote national courts' development and capacity building in processing and adjudicating international crimes. AbstrakPenerapan yurisdiksi Mahkamah Pidana Internasional memiliki konsekuensi terhadap eksistensi pengadilan nasional dalam mengadili kejahatan internasional. Mahkamah Pidana Internasional memiliki otoritas untuk mengadili kejahatan tertentu seperti genosida, kejahatan terhadap kemanusiaan, kejahatan perang dan kejahatan agresi. Namun, terbentuknya Mahkamah Pidana Internasional tidak menghilangkan kewajiban pengadilan nasional untuk memproses dan mengadili pelaku kejahatan tersebut. Tulisan ini mengkaji mengenai konsekuensi yuridis yang timbul dari penerapan yurisdiksi Mahkamah Pidana Internasional terhadap eksistensi pengadilan nasional dalam mengadili pelaku kejahatan internasional. Metode penelitian yang digunakan dalam artikel ini adalah penelitian normatif. Hasil penelitian menunjukkan bahwa penerapan yurisdiksi Mahkamah Pidana Internasional sangat penting untuk mengatasi impunitas dalam kejahatan internasional dan merupakan isu global yang relevan. Mahkamah Pidana Internasional bertindak sebagai pelengkap dan hanya intervensi ketika pengadilan nasional tidak efektif. Konsekuensi yuridis dari penerapan yurisdiksi Mahkamah Pidana Internasional terhadap pengadilan nasional melibatkan kolaborasi dan koordinasi antara kedua pengadilan untuk mencapai hasil yang adil dan efektif bagi terdakwa dan korban. Untuk itu perlu mendorong pengembangan dan peningkatan kapasitas pengadilan nasional dalam memproses dan mengadili kejahatan internasional.